2014
DOI: 10.1002/app.41645
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the coagulation medium on the performance of poly(ether sulfone) flat‐sheet membranes

Abstract: Poly(ether sulfone) flat-sheet membranes were fabricated via phase inversion with different nonsolvent mixtures. The effect of the nonsolvent water with the addition of various amounts of ethanol, acetone, or isopropyl alcohol on the membrane morphology (as measured with scanning electron microscopy and atomic force microscopy) and the filtration performance were investigated. For the statistical evaluation of the fabrication process, on average, six membranes were produced. The pure water flux (PWF) and macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This is consistent with a study by Misdan et al [ 41 ], who observed higher roughness of PA-coated membranes. Moreover, in a previous study [ 40 ] on the effect of coagulation medium composition, it was not possible to identify a clear trend in the surface structures with the addition of ethanol to the coagulation bath, which is confirmed in the presented AFM plots and data.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…This is consistent with a study by Misdan et al [ 41 ], who observed higher roughness of PA-coated membranes. Moreover, in a previous study [ 40 ] on the effect of coagulation medium composition, it was not possible to identify a clear trend in the surface structures with the addition of ethanol to the coagulation bath, which is confirmed in the presented AFM plots and data.…”
Section: Resultsmentioning
confidence: 52%
“…Both uncoated fibres show no salt rejection due to their UF characteristics. The higher permeate flux of the uncoated membrane prepared with pure water is attributed to fast demixing in the phase inversion process, whereas delayed demixing takes place when fractions of organic additives (ethanol) are added to the internal coagulation medium, resulting in denser support structures and lower flux [ 40 ]. The preparation procedure of support MCM was relatively robust, as independent preparation of MCM resulted in a relative standard deviation of permeate flux at 1 bar of 4.4% ( n = 4, post-treatment (PT) in 5000 ppm NaClO: one day) for BF W100 and 3.9% ( n = 3, PT one day) for BF W80E20, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of additive and adjustment of polymer concentration in casting dope are known to efficiently control the thin film morphology in enhancing the film performances. The additives can be water, inorganic additives, low‐molecular‐weight organics, surfactants, polymers, mineral filters, or a mixture of them . Ahmad et al .…”
Section: Introductionmentioning
confidence: 99%